2012
DOI: 10.1371/journal.pone.0050850
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CB1 Cannabinoid Receptor by Lentivirus Mediated Small Interfering RNA Ameliorates Hepatic Fibrosis in Rats

Abstract: It is recognized that endogenous cannabinoids, which signal through CB1 receptors in hepatic stellate cells (HSCs), exert a profibrotic effect on chronic liver diseases. In this study, we suppressed CB1 expression by lentivirus mediated small interfering RNA (CB1-RNAi-LV) and investigated its effect on hepatic fibrosis in vitro and in vivo. Our results demonstrated that CB1-RNAi-LV significantly inhibited CB1 expression, and suppressed proliferation and extracellular matrix production in HSCs. Furthermore, CB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In addition to mitigating predisposing factors, CB 1 R blockade can also directly engage profibrotic gene expression and signaling in the liver, inhibition of which has been shown to contribute to the therapeutic efficacy of CB 1 R blockade (11, 4346), cnr1 gene deletion (47), or RNAi-mediated cnr1 knockdown (48) in models of liver fibrosis without underlying obesity. Furthermore, CB 1 R antagonism increases the expression of matrix metalloprotease-1 (49) involved in extracellular matrix degradation and decreases the expression of its inhibitor TIMP1 (43) and could thus promote fibrosis reversal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mitigating predisposing factors, CB 1 R blockade can also directly engage profibrotic gene expression and signaling in the liver, inhibition of which has been shown to contribute to the therapeutic efficacy of CB 1 R blockade (11, 4346), cnr1 gene deletion (47), or RNAi-mediated cnr1 knockdown (48) in models of liver fibrosis without underlying obesity. Furthermore, CB 1 R antagonism increases the expression of matrix metalloprotease-1 (49) involved in extracellular matrix degradation and decreases the expression of its inhibitor TIMP1 (43) and could thus promote fibrosis reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal afferents from pulmonary and upper airway tissues synapse in the nucleus of the solitary tract (NTS) [41] , [42] , which is part of the respiratory circuitry including the ponto-medullary pattern generator that projects to the phrenic and hypoglossal motor nuclei [43] . Different areas of the NTS stimulated with L-glutamate lead to different patterns of respiratory responses [42] , and CB receptors are located presynaptically on first-order glutamatergic vagal afferent neurons and on second-order GABAergic neurons in NTS [44] , [45] . It is feasible that systemic pre-treatment with CB receptor antagonists can increase genioglossus activity through modulation of first- and/or second-order NTS neurons that project to hypoglossal motoneurons, but does not affect phrenic motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Then, there is a correlation between Collagen expressions that decrease and fibrosis reduction in treated animals. Other authors, had also demonstrated that blocking of CB1 mRNA reduces collagen I expression in a cirrhosis experimental model [27]. Among other crucial cytokines involved in fibrogenesis, TGF-β1 stimulates the production of Col I. pshCB1-B-mediated blocking decreased significantly TGFβ-1 levels (P <0.05), data that are consistent with previous studies by Yang YY et al, in which treatment with AM-251 (CB1 antagonist) inhibits the hepatic expression of TGFβ -1 in cirrhotic livers induced by bile duct ligation [13].…”
Section: Discussionmentioning
confidence: 92%
“…Our aim is to limit transfection to hepatic tissue and silence the CB1 gene without adverse effects in SCN. Other strategies focus on reducing the expression of CB1 or blocking its signal transduction pathway to reduce hepatic fibrosis has been probed [27,28]. Nonetheless, the drugs had demonstrated important behavior adverse effects and silencing using lentivirus as vectors is still not completely safe due to its random integration in the genome.…”
Section: Discussionmentioning
confidence: 99%